2016
DOI: 10.1108/jeee-08-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

The impact of entrepreneurship on knowledge economy in Africa

Abstract: Purpose -The paper assesses how entrepreneurship affects knowledge economy (KE) in Africa.Design/methodology/approach -Entrepreneurship is measured by indicators of starting, doing and ending business. The four dimensions of the World Bank's index of KE are employed. Instrumental variable panel fixed effects are applied on a sampled of 53 African countries for the period 1996-2010.Findings -The following are some findings. First, creating an enabling environment for starting business can substantially boost mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 101 publications
(158 reference statements)
8
59
1
Order By: Relevance
“…The narrative is in accordance with a recent strand of literature on soft economics (i.e. the human side of economic activities) (Kuada, 2015) and knowledge economy (Asongu, 2015a;Tchamyou, 2015;Asongu & Tchamyou, 2016).…”
Section: Asongu (2013a)supporting
confidence: 75%
“…The narrative is in accordance with a recent strand of literature on soft economics (i.e. the human side of economic activities) (Kuada, 2015) and knowledge economy (Asongu, 2015a;Tchamyou, 2015;Asongu & Tchamyou, 2016).…”
Section: Asongu (2013a)supporting
confidence: 75%
“…For example, it has been noted that the poor state of infrastructure in Nigerian universities cannot support the newly introduced entrepreneurship education (Nwekeaku, 2013;Oviawe, 2010). On the other hand, Asongu and Tchamyou (2016) found that there is an inverse relationship between the time required to start a business and the level of innovation. An aspiring entrepreneur may be dissuaded by several bureaucratic huddles which must be crossed in starting a business.…”
Section: Conversion Factors In Business Incubation and Entrepreneurshmentioning
confidence: 99%
“…These include research in the area of capability approach, functionings, freedoms or capabilities, business incubation and entrepreneurship development (Al-Mubaraki and Busler, 2010;Alkire, 2002;Charles and Ikenna, 2009;Asongu and Tchamyou, 2016;European Commission, 2002;Gedeon, 2010;Isaacs et al, 2007;Lalkaka, 2003;Lee and Peterson, 2000;Lee et al, 2005;Lin et al, 2011;Morris et al, 2013;Nwekeaku, 2013;Aja-Okorie and Adali, 2013;Okpara et al, 2011;Oviawe, 2010;Ratten, 2014;Robeyns, 2000Robeyns, , 2005Sen, 1992;Somsuk et al, 2012;Varadjanin et al, 2014). The following sections provide a summary of literature on the capability approach and entrepreneurship education at a global level in general and Nigeria in particular.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The policy relevance of the inquiry is twofold. On the one hand, the growing relevance of knowledge economy in 21 st century development we have discussed in the first paragraph (also see Asongu and Tchamyou, 2016). On the other hand, the contribution of SSA's trade to the global economy has declined considerably.…”
Section: Development In the 21mentioning
confidence: 97%